Transcriptomic Analysis Reveal the Molecular Mechanisms of Seed Coat Development in Cucurbita pepo L. - Xue, Yingyu; Shen, Zhiyan; Tao, Fei; Zhou, Jingjiang; Xu, Bingliang (Frontiers in Plant Science, 2022)
Cucurbita pepo is one of the earliest cultivated crops. It is native to Central and South America and is now widely cultivated all over the world for its rich nutrition, short growth period, and high yield, which make it suitable for intercropping. Hull-less C. pepo L. (HLCP) is a rare variant in nature that is easier to consume. Its seed has a seed kernel but lacks a seed coat. The molecular mechanism underlying the lack of seed coat development in the HLCP variety is not clear yet. The BGISEQ-500 sequencing platform was used to sequence 18 cDNA libraries of seed coats from hulled C. pepo (CP) and HLCP at three developmental stages (8, 18, and 28 d) post-pollination. We found that lignin accumulation in the seed coat of the HLCP variety was much lower than that of the CP variety, and that the seed coat of the HLCP variety lacked the hypodermis and sclerenchyma tissue layers. A total of 2099 DEGs were identified in the CP variety, which were enriched mainly in the phenylpropanoid biosynthesis pathway, amino sugar, and nucleotide sugar metabolism pathways. A total of 1831 DEGs were identified in the HLCP variety and found to be enriched mainly in the phenylpropanoid biosynthesis and metabolism pathways of starch and sucrose. Among the DEGs, hub proteins (FusA), protein kinases (IRAK4), and several transcription factors related to seed coat development (MYB, bHLH, NAC, AP2/EREBP, WRKY) were upregulated in the CP variety. The relative expression levels of 12 randomly selected DEGs were determined using quantitative real-time PCR analysis and found to be consistent with those obtained using RNA-Seq, with a correlation coefficient of 0.9474. We found that IRAK4 protein kinases, AP2/EREBP, MYB, bHLH, and NAC transcription factors may play important roles in seed coat development, leading to the formation of HLCP.